2017
DOI: 10.1038/srep43985
|View full text |Cite
|
Sign up to set email alerts
|

Targeted antigen delivery to dendritic cells elicits robust antiviral T cell-mediated immunity in the liver

Abstract: Hepatotropic viruses such as hepatitis C virus cause life-threatening chronic liver infections in millions of people worldwide. Targeted in vivo antigen-delivery to cross-presenting dendritic cells (DCs) has proven to be extraordinarily efficient in stimulating antigen-specific T cell responses. To determine whether this approach would as well be suitable to induce local antiviral effector T cells in the liver we compared different vaccine formulations based on either the targeting of DEC-205 or TLR2/6 on cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Dendritic cells manipulation has also been proposed. Indeed, administration of HBV peptide-loaded DCs was reported to elicit functional HBV-specific CD8 cells and to reduce the viral load in Hepato-HuPBL mice (138) and a targeted antigen delivery to DCs was proven to efficiently induce local immunity to hepatotropic viruses in mice (139). Interestingly, in the context of cancer immunotherapy, PD-L1 silenced DCs were used for a DC vaccine that induced potent T cell responses (140).…”
Section: Tolerogenic Apcmentioning
confidence: 99%
“…Dendritic cells manipulation has also been proposed. Indeed, administration of HBV peptide-loaded DCs was reported to elicit functional HBV-specific CD8 cells and to reduce the viral load in Hepato-HuPBL mice (138) and a targeted antigen delivery to DCs was proven to efficiently induce local immunity to hepatotropic viruses in mice (139). Interestingly, in the context of cancer immunotherapy, PD-L1 silenced DCs were used for a DC vaccine that induced potent T cell responses (140).…”
Section: Tolerogenic Apcmentioning
confidence: 99%
“…The literature also shows that HSP90 can stimulate DCs and induce CTL polarization and activation [ 16 ]. A study showed that cross-presenting DCs is highly effective in inducing CTLs capable of eliminating liver cancer [ 17 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Subsequently, cells were permeabilized (0.1% IGEPAL CA‐630 (Sigma‐Aldrich), 4 min, 4°C), washed and stained with anti‐IFN‐γ‐APC (XMG1.2), anti‐IL‐2‐PE (JES6‐5H4) or anti‐TNF‐α‐APC (MPC‐XT22) (BioLegend) for 30 min at 4°C. IκB NS ‐dependency of cytotoxic function in CD8 + T cells was determined as described before . Cells were analyzed with a BD FACS Canto II, BD LSR II (BD Biosciences) or an Attune NxT Acoustic Focusing Cytometer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%